2013
DOI: 10.2147/ndt.s53853
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of Nintendo Wii Fit PlusTM training in children with migraine without aura: a preliminary study

Abstract: BackgroundMigraine without aura (MoA) is a painful syndrome, particularly in childhood; it is often accompanied by severe impairments, including emotional dysfunction, absenteeism from school, and poor academic performance, as well as issues relating to poor cognitive function, sleep habits, and motor coordination.Materials and methodsThe study population consisted of 71 patients affected by MoA (32 females, 39 males) (mean age: 9.13±1.94 years); the control group consisted of 93 normally developing children (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 89 publications
0
14
0
4
Order By: Relevance
“…Overall, the qualitative review of these studies supports a positive effect of Wii Fit interventions on balance outcomes. Among the 55 studies, 50 observed a positive effect of Wii Fit on at least one parameter ( Morone et al, 2014 ; Wall et al, 2015 ; Bieryla & Dold, 2013 ; Rendon et al, 2012 ; Bainbridge et al, 2011 ; Fung et al, 2012 ; Salem et al, 2012 ; Barcala et al, 2013 ; Yatar & Yildirim, 2015 ; Meldrum et al, 2015 ; Ferguson et al, 2013 ; Hammond et al, 2014 ; Mombarg, Jelsma & Hartman, 2013 ; Jelsma et al, 2013 , 2014 ; Esposito et al, 2013 ; Tarakci et al, 2013 ; Gioftsidou et al, 2013 ; Melong & Keats, 2013 ; Lee, Lee & Park, 2014 ; Cone, Levy & Goble, 2015 ; Baltaci et al, 2013 ; Sims et al, 2013 ; Punt et al, 2015 ; Brichetto et al, 2013 ; Nilsagård, Forsberg & von Koch, 2013 ; Prosperini et al, 2013 ; Robinson et al, 2015 ; Hung et al, 2014 ; Omiyale, Crowell & Madhavan, 2015 ; Williams et al, 2011 ; Bateni, 2012 ; Orsega-Smith et al, 2012 ; Toulotte, Toursel & Olivier, 2012 ; Chao et al, 2013 , 2014 ; Cho, Hwangbo & Shin, 2014 ; Nicholson et al, 2015 ; Roopchand-Martin et al, 2015 ; Williams et al, 2010 ; Agmon et al, 2011 ; Jorgensen et al, 2013 ; Esculier et al, 2012 ; dos Santos Mendes et al, 2012 ; Padala et al, 2012 ; Pompeu et al, 2012 ; Mhatre et al, 2013 ; Esculier, Vaudrin & Tremblay, 2014 ; Goncalves et al, 2014 ; …”
Section: Resultsunclassified
“…Overall, the qualitative review of these studies supports a positive effect of Wii Fit interventions on balance outcomes. Among the 55 studies, 50 observed a positive effect of Wii Fit on at least one parameter ( Morone et al, 2014 ; Wall et al, 2015 ; Bieryla & Dold, 2013 ; Rendon et al, 2012 ; Bainbridge et al, 2011 ; Fung et al, 2012 ; Salem et al, 2012 ; Barcala et al, 2013 ; Yatar & Yildirim, 2015 ; Meldrum et al, 2015 ; Ferguson et al, 2013 ; Hammond et al, 2014 ; Mombarg, Jelsma & Hartman, 2013 ; Jelsma et al, 2013 , 2014 ; Esposito et al, 2013 ; Tarakci et al, 2013 ; Gioftsidou et al, 2013 ; Melong & Keats, 2013 ; Lee, Lee & Park, 2014 ; Cone, Levy & Goble, 2015 ; Baltaci et al, 2013 ; Sims et al, 2013 ; Punt et al, 2015 ; Brichetto et al, 2013 ; Nilsagård, Forsberg & von Koch, 2013 ; Prosperini et al, 2013 ; Robinson et al, 2015 ; Hung et al, 2014 ; Omiyale, Crowell & Madhavan, 2015 ; Williams et al, 2011 ; Bateni, 2012 ; Orsega-Smith et al, 2012 ; Toulotte, Toursel & Olivier, 2012 ; Chao et al, 2013 , 2014 ; Cho, Hwangbo & Shin, 2014 ; Nicholson et al, 2015 ; Roopchand-Martin et al, 2015 ; Williams et al, 2010 ; Agmon et al, 2011 ; Jorgensen et al, 2013 ; Esculier et al, 2012 ; dos Santos Mendes et al, 2012 ; Padala et al, 2012 ; Pompeu et al, 2012 ; Mhatre et al, 2013 ; Esculier, Vaudrin & Tremblay, 2014 ; Goncalves et al, 2014 ; …”
Section: Resultsunclassified
“…In this light, using virtual environments can be identified as beneficial to the efficiency and outcome of rehabilitative program in children with disabling medical conditions or lower level of physical fitness. 27 Moreover, considering that children with migraine are identified as less inclined to engaging in physical activities, 27 stimulating them through exergaming and/or software training (active computer games), which they enjoy, may be useful to promote their motor skills. On the other hand, many reports showed specific links between neuropsychological impairment and neuroimaging findings in migraine subjects in both adults and children.…”
Section: Discussionmentioning
confidence: 99%
“… 25 Moreover, Esposito et al 11 reported the association between poor motor coordination and MwA in children suggesting a role of impairment in perceptual organization abilities of children with MwA as the cause for motor coordination and visual–motor integration (VMI) impairment of these subjects. 26 In this context, we previously proposed a new rehabilitation approach to these conditions in children affected by MwA, 27 suggesting a positive role of exergames in motor coordination improvement, although only partial improvement in VMI abilities has been obtained.…”
Section: Introductionmentioning
confidence: 99%
“…However, primary health care providers need strategies to improve their ability to counsel patients effectively 12,13. New technologies can be applied to support health care interventions in all age groups 1416. In the It’s LiFe!…”
Section: Introductionmentioning
confidence: 99%